Evaluation of the Impacts of Service Quality Dimensions on Patient/Customer Satisfaction: A Study of Private Hospitals in Nepal - Neupane, Ramesh; Devkota, Manju (International Journal of Social Sciences and Management, 2017)
The main purpose of this research is to examine the impacts of service quality dimensions on patient satisfaction as a study of private hospitals in Nepal. This research has also evaluated the perceptions of the patients about service quality offered by private hospitals and level of their satisfaction. The research was conducted through influence of positivism philosophy and deductive approach. The two hypotheses were generated with the help of existing knowledge and literature related to service quality and customer/patient satisfaction. The formulated hypotheses were tested through primary data collection from the customers/patients of private hospitals in Nepal. The questionnaires survey was used to collect data in this study. Different five factors of SERVQUAL dimension and four factors of patient satisfaction: price, image, perceived quality and convenience were used to analyse service quality and patient satisfaction respectively. Samples of 490 patients from different 10 private hospitals which all are based on Kathmandu were considered in the study. The results indicated that each dimension of service quality is positively correlated with patient satisfaction, and overall service quality and patient satisfaction has correlation coefficient of 0.719 which is significant at the 0.01 level. This implies that service quality and patient satisfaction are positively correlated with each other. The results demonstrated that service quality has strong positive impacts on patient satisfaction as regression analysis demonstrates that service quality has significant impacts on patient satisfaction as β = 0.719 and P = 0.000 which is less than 0.05. Similarly, the results also indicated that private hospitals in Nepal are providing high level of service quality in the view of patients/customers; and there is high level of patient satisfaction at the private hospitals in Nepal. Int. J. Soc. Sc. Manage. Vol. 4, Issue-3: 165-176